Repurposing the University in Times of Social and Ecological Breakdown: From the Ivory Tower to the Nurse Log - Stein, Sharon; de Oliveira Andreotti, Vanessa (Canadian Journal of Education / Revue canadienne de l'éducation, 2025)
This article considers how universities might be repurposed to fulfill their responsibilities to future generations in the context of accelerating social and ecological breakdown. To do so, we invite readers into an inquiry about how educators might prepare ourselves and our students to navigate current and coming disruptions in ways that interrupt enduring cycles of violence and unsustainability through processes of redistribution, reparation, restitution, and regeneration. We propose shifting metaphors from universities as elitist ivory towers to humble nurse logs that could support the composting of the current system and nourish emerging possibilities for education and existence. To illustrate this possibility, we consider two experimental efforts to repurpose higher education toward intergenerational and interspecies responsibility.